Islamic Education Innovation Management to Improve the Quality and Competitiveness of Maqashid Shariah-Based Institutions - Asyha, Agus Faisal; Pahrudin, Agus; Yuberti, Yuberti; Rinaldi, Achi; Warsiyah, Warsiyah (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2025)
This article comprehensively reviews the literature on systematic strategies for managing Islamic educational innovations aligned with the principles of sharia maqashid to improve learning quality and the competitiveness of Islamic educational institutions in Indonesia. The method used is a literature review with theoretical synthesis, research findings, and innovative practices grounded in Sharia maqashid, drawing on 23 articles. The literature databases used are Google Scholar and Scopus, which cover innovation management, Islamic education, sharia maqashid, and educational challenges and opportunities in the digital era. The focus of data collection is on literature published in the last 5 years. A study of 23 articles shows that the management of Islamic educational innovation generally includes the stages of identifying needs, designing strategies, implementing, evaluating, and replicating programs, which, in much of the literature, are guided by the principles of maqashid sharia as an ethical and strategic foundation. The widely discussed innovation trends include developing a curriculum grounded in Islamic competencies and values, leveraging digital technology, adopting active learning models, and strengthening institutional governance, while encouraging Islamic character development and sharia entrepreneurship to improve the quality of graduates holistically. Although the literature identifies several conceptual and structural challenges, a synthesis of studies indicates that innovations grounded in sharia maqashid have significant potential to enhance the quality and competitiveness of Islamic educational institutions. The contribution of this paper lies in integrating these findings into a more systematic theoretical framework, offering a new conceptual mapping of how the Sharia maqashid can direct innovation as a strategy to strengthen the quality and competitive advantage of Islamic educational institutions in the modern era.